AN EXPLORATORY STUDY ON THE HOUSING NEEDS OF SINGLE WOMEN IN PRE-OLD AGE -A CASE STUDY OF TAINAN, TAIWAN - Huang, Kan-Chung; Lin, Linda Lin-Chin; Chiu, Jo-Hua; Sung, Mei-Chih; Wu, Mei-Shu (International Journal of Application on Economics and Business, 2025)
Taiwan is set to enter a super-aged society by 2025, and the proportion of single-person households is gradually increasing—particularly among never-married, single women living alone. As the aging population grows, some prior studies have explored topics such as housing arrangements and intergenerational support for older adults. However, research on the housing choices of older individuals living alone remains limited. Most elderly people in Taiwan live in homes over 30 years old, and the combination of aging individuals and aging buildings often creates a form of "involuntary confinement" for those with mobility issues. Additionally, age-based discrimination in the rental housing market poses significant challenges, making it crucial for policymakers to address the housing choices available to older adults living alone.This study aims to explore the current housing situations of never-married women in their pre-old age (aged around 50–64), as well as their expectations and preferences for housing in later life. It specifically focuses on the possibility of homeownership and the factors influencing their decision to purchase property. A structured questionnaire was developed and distributed via snowball sampling through social media platforms, and data collection was completed in April 2024 in Tainan City. Key findings include: (1) A high proportion (51.30%) of early home purchases were in walk-up row houses without elevators, making "lack of elevators" the primary reason for wanting to move. About 68.70% of respondents expressed a desire to move to housing more suitable for retirement; (2) Despite this, many respondents (62.60%) preferred not to relocate outside their current daily living area due to familiarity with their routines. However, if a home met their ideal living conditions for later life, they were less concerned with "aging in place" or being close to children or relatives (only 28.70% prioritized proximity to family); (3) "Condominiums/apartment buildings" were the preferred housing type for most respondents (53.04%), especially "new builds within 1–5 years" and "previously owned homes" (73.05%). The most important factor influencing choice was "access to daily necessities and services (e.g., shopping, medical care)" (57.39%); (4) Apartment-style buildings are increasingly favored, particularly those with a moderate number of units and a clear, non-mixed community structure. Most respondents preferred three-bedroom, two-living-room layouts, followed by two-bedroom options. About 61.43% preferred a total floor area of 21–40 ping (approximately 74–132 square meters), avoiding very small units. Notably, 32.85% preferred homes over 40 ping, suggesting that some respondents with better financial means favor larger living spaces; (5) The top factors influencing home purchase decisions were total price, living convenience, layout, transportation accessibility, and building materials/safety.